Estudo teórico-computacional das propriedades eletrônicas, ópticas e ferroelétricas dos compostos multifuncionais R3c AFeO3 (A= Sc ou In) - Souza, Jonathan Silva (2023)
The search for materials with adequate ferroelectric and photovoltaic properties is an intense field of research in Physics of Materials. Employing calculations based on noncollinear spin density functional theory, we investigate the electronic, optical and ferroelectric properties of the multifunctional R3c AFeO3 (A = Sc or In) compounds. The main objective of this study is to better understand, from the point of view of fundamental properties, the potential of these materials for photovoltaic applications, especially in the field of ferroelectric-photovoltaics. Due to the lack of experimental information about these properties, we used those of an isostructural compound (R3c BiFeO3), which are well documented in the literature as a reference for choosing the Ueff value to be applied in the calculations. Therefore, to approximate the exchange and correlation electronic effects in our calculations, the local spin density approximation including the effective Hubbard U correction (Ueff = 6.0 eV) was used for the 3d states of the Fe atom. It was determined that the ScFeO3 and InFeO3 compound exhibit direct energy band gaps of 3.0 eV and 2.6 eV, respectively, and absorb visible light in the extreme part of the visible solar spectrum. The effective masses of the charge carriers (m*) are comparable to those of conventional commercial semiconductors (m* ≤ 0.5 m0) and the values of excitons dissociation energies are low (< 2.0 meV). All these properties are comparable to those of BiFeO3, which is a material widely used in photovoltaic applications. Therefore, the R3c ScFeO3 and InFeO3 compound have great potential to be used for future photovoltaic applications. Aiming at adjusting the properties of interest of the InFeO3 compound, self-consistent calculations of the material under tension and compression in the volume of the unit cell were performed. Our studies revealed that under tensile strain conditions in the unit cell volume, this material presents an ideal energy band gap for photovoltaic applications. In other words, under tensile strain of 9% of the unit cell volume of R3c InFeO3 (a = 5.536 Å and c = 13.808 Å), a direct energy band gap of 1.74 eV was found. For this crystalline structure, it was also verified that the material reaches a maximum photoconversion efficiency of 20% for a thin film thickness of approximately 100 nm. This value is 4% higher than that of tension-free material. It was also found that the effective mass of the charge carriers and the exciton binding energy are significantly decreased relative to that of the stress-free material. These last two facts will probably lead to better mobility of charge carriers and easier separation of the electron-hole pair in the material's light photoabsorption process. Under this strain level, the spontaneous electrical polarization was reduced to 77.6 μC/cm2 which is a value even higher than that of other known ferroelectric materials.